Digital Literacy Ability of Students of Biology Education Study Program FSTT Undikma - Herdiyana Fitriani; Taufik Samsuri; M Zainuddin (Postgraduate, University of Mataram, 2023)
This study aims to understand the condition of digital literacy skills of S1 students of the biology education study program, Faculty of Science, Engineering and Applied (FSTT) Mandalika University of Education (Undikma). Cross-sectional study with a survey method that aims to analyze variable data collected at a certain point in time throughout the sample population or a predetermined subset. The population of this study is all active Biology Education study program students as many as 212 students. The research sample amounted to 86 students as respondents obtained by accidental sampling techniques. This research instrument is in the form of a google form-based student digital literacy mastery questionnaire, which is given online. The results of the study on each indicator are the Access indicator of 58.1% of students' goals to access the internet to complete assignments, 91.9% using mobile phone media, 40% using subjects as search points, and 67% using complete search keywords to access information from the internet. In the Analyze and Evaluate indicator, 60.5% read and understand the information thoroughly and 48.98% read the information thoroughly and the sources used. In the Create indicator, the new form of information created by students is with 41.9% making research reports, 36.0% using Microsoft Office devices, and 51.2% in the form of writing. The Reflect indicator is the largest percentage of respondents to respect and maintain a code of ethics when accessing information accessed from the internet with a magnitude of 65.1% listing the source of information cited appropriately and 75.6% ensuring the correctness of the information and using as needed. Indiator Act, the actions of college students after accessing and using the internet with 46.5% using information to solve problems and 34.9% to make presentations in public. Based on this description, it can be concluded that students' digital literacy skills have reached the good category